2022
DOI: 10.3390/cells11071108
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Remodeling in the Absence of Cardiac Contractile Dysfunction Is Sufficient to Promote Cancer Progression

Abstract: Cardiovascular diseases and cancer are the leading cause of death worldwide. The two diseases share high co-prevalence and affect each other’s outcomes. Recent studies suggest that heart failure promotes cancer progression, although the question of whether cardiac remodeling in the absence of cardiac contractile dysfunction promotes cancer progression remains unanswered. Here, we aimed to examine whether mild cardiac remodeling can promote tumor growth. We used low-phenylephrine (PE)-dose-infused in mice, toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
(29 reference statements)
1
12
0
Order By: Relevance
“…Currently, tumor promotion phenotype was apparent with multiple mice models such as myocardial infarction (MI) [16][17][18], pressure overload (TAC) [10], and heart hypertrophy (ATF3 transgene) [11]. In addition, a chronic hypertension model with heart hypertrophy but no cardiac dysfunction resulted in enhanced tumor growth [19]. Therefore, based on the lack of tumor promotion in MDX mice, we conclude that the tumor promotion phenotype is rather dependent on the cardiac hypertrophy phenotype and independent of direct cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, tumor promotion phenotype was apparent with multiple mice models such as myocardial infarction (MI) [16][17][18], pressure overload (TAC) [10], and heart hypertrophy (ATF3 transgene) [11]. In addition, a chronic hypertension model with heart hypertrophy but no cardiac dysfunction resulted in enhanced tumor growth [19]. Therefore, based on the lack of tumor promotion in MDX mice, we conclude that the tumor promotion phenotype is rather dependent on the cardiac hypertrophy phenotype and independent of direct cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…While heart failure and cancer have until recently been considered separate diseases, it is becoming evident that they are highly connected and affect each other's outcome at multiple levels (3)(4)(5)(6). In particular, several recent studies using multiple mouse models for heart failure demonstrated that heart failure following myocardial infraction (7,8), and even early cardiac remodeling prior to heart failure, promote cell proliferation and cancer cell migration (9)(10)(11) and metastasis seeding (3,9,12). In addition, multiple epidemiological studies have suggested that myocardial infraction patients are at a higher risk of developing cancer with a poorer outcome (13), and the same goes for young patients with severe aortic stenosis (12,14).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests cardiac remodeling and cancer progression are tightly linked (Avraham et al, 2020 ). This link goes both ways: heart failure or cardiovascular disease enhances existing (Koelwyn et al, 2020 ) or new (Avraham et al, 2020 ; Awwad et al, 2022 ) tumor growth, and the onset of cancer increases incidents of atrial fibrillation and other cardiac abnormalities (Conen et al, 2016 ; Guzzetti et al, 2002 ). In this study, we show the effects of cancer on the heart, specifically HRV and cardiac structure, using pancreatic and liver cancer models.…”
Section: Introductionmentioning
confidence: 99%